Accounting for taste? Analysing diverging public support for energy sources in Great Britain. (October 2019) - Roddis, Philippa; Carver, Stephen; Dallimer, Martin; Ziv, Guy
Highlights: We analyse a large dataset on public attitudes in Great Britain over six years. We develop and test five hypotheses based on a novel conceptual framework. We chart spatial and temporal trends in public support for eight energy sources. We identify a growing divide between support for renewable and non-renewable energy. Our results help to understand and explain public acceptance at a national scale. Abstract: Public acceptance of energy technologies is an important area of energy and social science research. However, few studies utilise large datasets which include spatial and temporal dimensions, as well as the demographic and attitudinal characteristics of survey respondents. In this paper, we analyse twenty-five waves of the UK Government's Energy and Climate Change Public Attitudes Tracker: a large, nationally representative dataset spanning six years (2012 - 2018). This enables unique insights into trends in public acceptance across time, space and social groups, covering eight energy sources. We find differing profiles in terms of who supports which types of energy, with a key division between support for renewable technologies on the one hand, and nuclear and fracking on the other. We also identify a growing gap between public and policymakers' attitudes to energy technologies which we argue must be bridged to ensure a smooth rapid transition that is acceptable to all.